(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: One of the problems experienced by drug addicts is the loss of confidence due to the effects of taking drugs. One of the techniques used in anti-drug rehabilitation dip is to use motivational interviewing techniques. This technique aims to motivate addicts to change. This study aims to know the confidence of drug addicts when newly entered Community-Based Rehabilitation, to see the process of motivational interviewing (MI) techniques in Community-Based Rehabilitation and to see the role of motivational interviewing (MI) techniques. Materials and Method: The data used is qualitative. The subjects of this study were three drug addicts and one counsellor. The data sources taken in this study are primary and secondary data sources. The data was obtained using interview methods, observation methods and documentation methods. Qualitative data analysis techniques consist of four stages: data reduction, presentation of data (data display), conclusion drawing and verification. From the results of research obtained confidence addict drugs when new to Community-Based Rehabilitation that is, often alone, being close to others, silent, and consistently negative thinking (negative thinking) towards others, feeling afraid, unsure of themselves, always being negative, reluctant to communicate, not serious, irresponsible, closed and pessimistic about what he does. Result: In Community-BasedRehabilitation, the four principles are carried out: expressing empathy, developing discrepancy, accepting resistance, and supporting efficacy. Conclusions: Motivational interviewing (MI) techniques play a role in overcoming the confidence of drug addicts with changes in attitudes and ways of thinking, changes experienced that is, clients are more serious, responsible, think and be positive, open to others, optimistic, rational thought, and better understand the feelings of themselves and others.